"The Read-Out Driver" ROD card for the Insertable B-layer (IBL) detector of the ATLAS experiment: commissioning and upgrade studies for the Pixel Layers 1 and 2 - Balbi, Gabriele; Bindi, M.; Chen, S. P.; Falchieri, D.; Flick, T.; Gabrielli, A.; Hauck, S.; Hsu, S. C.; Kretz, Moritz; Kugel, Andreas; Lama, L.; Morettini, P.; et al. (Journal of Instrumentation, 2014)
The upgrade of the ATLAS experiment at LHC foresees the insertion of an innermost silicon layer, called the Insertable B-layer (IBL). The IBL read-out system will be equipped with new electronics. The Readout-Driver card (ROD) is a VME board devoted to data processing, configuration and control. A pre-production batch has been delivered for testing with instrumented slices of the overall acquisition chain, aiming to finalize strategies for system commissioning. In this paper system setups and results will be described, as well as preliminary studies on changes needed to adopt the ROD for the ATLAS Pixel Layers 1 and 2.
Gesehen am 03.11.2020